Odpowiedzi

2010-01-07T14:33:10+01:00
1) 2(a+b)-(a-b)/2= [4(a+b)-(a-b)]/2=
[4a+4b-a+b]/2=
[3a+5b]/2

gdy a =-4 i b=6

[-12+30]/2=18/2=9

2)(x²-4)-(9x²+6x+1)= x²-4-9x²-6x-1=-8x²-6x-5
dla x=-2
-8*4-6*(-2)-5= -32+12-5=-25

3)(10x-5x²-2+x)-(-5x²+x)=
11x-5x²-2+5x²-x= 10x-2
x=8/5

10*8/5-2=16-2=14

4)5(5x+2)=3(3x+6) wymnożyłam całość przez 15
25x+10=9x+18
16x=8/:16
x=1/2

5)2(2x+1)-3(3x-2)=6(2-x) wymnożone przez 6

4x+2-9x+6=12-6x
-5x+8=12-6x
x=4

6)2(x²-6x+9)-(16+8x+x²)=x²-6x
2x²-12x+18-16-8x-x²-x²+6x=0
-14x +2=0
-14x=-2
x=2/14=1/7
2010-01-07T14:43:14+01:00
1) a=-4, b=6
4*(a+b)/2-2*(a-b)/4=2*(a+b)-(1/2)*(a-b)=2*(-4+6)-(1/2)*(-4-6)=2*2-(1/2)*(-10)=4+5=9

2) x=-2
(x-2)(x+2)-(3x+1)²=(-2-2)*(-2+2)-(3x+1)²=-(3x+1)²=-(3*(-2)+1))²=-(-6+1)²=-(-5)²=-25

3) x=1⅗=8/5
(5x-1)(2-x)-x(-5x+1)=(5*8/5-1)(10/5-8/5)-8/5*(-5*8/5+1)=7*2/5-8/5*(-8+1)=14/5-8/5*(-7)=14/5+56/5=70/5=14

4) (5x+2)/3=(3x+6)/5 /*15
5*(5x+2)=3*(3x+6)
25x+10=9x+18 /-9x
25x-9x+10=18
16x+10=18 /-10
16x=8
x=8/16=1/2

5) (2x+1)/3-(3x-2)/2=2-x /*6
2*(2x+1)-3*(3x-2)=6*(2-x)
4x+2-9x+6=12-6x
-5x+8=12-6x /+6x
x+8=12
x=4

6) 2(x-3)²-(4+x)²=x(x-6)
2*(x²-6x+9)-(16+8x+x²)=x²-6x
2x²-12x+18-16-8x-x²=x²-6x
x²-20x+2=x²-6x /-x²
-20x+2=-6x /+20x
2=14x
x=2/14=1/7